Violência doméstica em João Pessoa: o impacto da pandemia da COVID-19 nas denúncias - Silva, Mariana Barbosa (2023)
Domestic violence is a complex issue that affects the physical, metal, and reproductive integrity of the victim, compromises the equal opportunities of these women in the labor market, and has a negative impact on the children who witnessed the aggression. The pandemic of COVID-19, the major global health crisis in recent times, has aggravated the cases of domestic violence in the world. One of the tools to combat COVID-19 was social distancing, or lockdown, in order to not only reduce the spread of the virus and lessen the burden on the healthcare system, but also trapped women victims of domestic violence at home with their abusers. Thus, the impact of social isolation due to the first wave of COVID-19 on reports of domestic violence at the Civil Police base in the city of Jo˜ao Pessoa was evaluated. In addition, a descriptive analysis of the data was performed, observing the profile of domestic violence reports and how they were distributed in the territory in the years 2019, 2020 and 2021. Jo˜ao Pessoa, capital of Para´ıba, the third oldest city in Brazil characterized by its colonial history, with the upper middle class located on the coast and the poorest in its interior, showed a higher concentration of domestic violence reports in the center-south zone, where the most populous lower middle class neighborhoods are located, and in the poorest peripheral zones. Finally, by the method of discontinuous regression, it is concluded that social isolation due to the pandemic had an impact of reducing up to 5,77 daily reports of domestic violence in the city, which does not necessarily mean a reduction in the prevalence of cases, but indicates that the lockdown collaborated to the increase of underreporting in reports of domestic violence in the city.